The NANOTUMOR consortium – Towards the Tumor Cell Atlas. (26th February 2021) - Colin, Florent; Schauer, Kristine; Hamiche, Ali; Martineau, Pierre; Borg, Jean‐Paul; Bednar, Jan; Bertolin, Giulia; Camoin, Luc; Collette, Yves; Dimitrov, Stephan; Fournier, Isabelle; Hyenne, Vincent; et al.
Abstract: Cancer is a multi‐step disease where an initial tumour progresses through critical steps shaping, in most cases, life‐threatening secondary foci called metastases. The oncogenic cascade involves genetic, epigenetic, signalling pathways, intracellular trafficking and/or metabolic alterations within cancer cells. In addition, pre‐malignant and malignant cells orchestrate complex and dynamic interactions with non‐malignant cells and acellular matricial components or secreted factors within the tumour microenvironment that is instrumental in the progression of the disease. As our aptitude to effectively treat cancer mostly depends on our ability to decipher, properly diagnose and impede cancer progression and metastasis formation, full characterisation of molecular complexes and cellular processes at play along the metastasis cascade is crucial. For many years, the scientific community lacked adapted imaging and molecular technologies to accurately dissect, at the highest resolution possible, tumour and stromal cells behaviour within their natural microenvironment. In that context, the NANOTUMOR consortium is a French national multi‐disciplinary workforce which aims at a providing a multi‐scale characterisation of the oncogenic cascade, from the atomic level to the dynamic organisation of the cell in response to genetic mutations, environmental changes or epigenetic modifications. Ultimately, this program aims at identifying new therapeutic targets using innovative drug design. Abstract : Review : NANOTUMOR is a French initiative whose objective is to map key ultrastructural and protein elements in cancer cells using multi‐resolution approaches. At the interface between molecular and structural biology, cell biology, as well as biosensor and drug design, this program aims to be the incubator of new and cross‐disciplinary collaborations, on a national scale and beyond. It will also initiate conferences and webinars on these themes (more information on https://www.nanotumor.fr/ ).